Pengaruh Pengaruh Penggunaan E-Commerce, Jumlah Pelanggan dan Modal Usaha Terhadap Pendapatan Pelaku UKM di Kota Denpasar - Marantiani, Desak Nyoman; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
Small and Medium Enterprises (SMEs) have an important and strategic role for the economic growth of the country, both developing and developed countries. The purpose of this research is to analyze the influence of simultaneous and partial use of e-commerce, the customers and venture capital to the income of SMEs in Denpasar City. Data used primary data. The samples used are 86 SMEs in Denpasar City. The analysis technique used is multiple linear regression analysis. The result show that simultaneously the variable of e-commerce usage, the customers and the business capital had a significant effect on the income of SMEs in Denpasar City. Partially the use of e-commerce, the customers and business capital have a positive and significant impact on the income of SMEs in the city of Denpasar.